EROSI DAN KEHILANGAN HARA PADA PERTANAMAN KENTANG DENGAN BEBERAPA SISTEM GULUDAN PADA ANDISOL DI HULU DAS MERAO, KABUPATEN KERINCI, JAMBI - H Henny; K Multilaksono; N Sinukaban; S D Tarigan (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2011)
This research was aimed to study alternative techniques for soil conservation in controlling erosion and nutirients lost from Andisol planted with potatoes in upper part of Merao watershed, in Kerinci Region, Jambi Province. The research was conducted in Kebun Baru, Kayu Aro, Kerinci. The soil and sediment samples were analysed at Soil and Land Resource Laboratory, Agriculture Faculty, Institute Pertanian Bogor. Erosion was measured on small plots consisting of seven (7) treatments and three (3) replications considered as blocks. The results showed that planting potatoes across the slope direction, or making soil bed across 15% slope, or soil bed as slope direction and across slope direction every 4.5 m distance could control erosion and nutrients lost, and did not affect potato yield compared to soil bed as slope direction. Planting potatoes on soil bed as slope and across slope direction in each 4,5 m distance (modified farmers model) reduced erosion, soil organic-C, and total-N lost for 65.89, 65.19, and 24.55%, respectively, compared to planting as slope direction. Keywords: erosion, nutrient lost, sedimentation